Triggers and patterns of integration initiatives in successful buyer–supplier relationships - Vanpoucke, Evelyne; Vereecke, Ann; Boyer, Kenneth K. (Journal of Operations Management, 2014)
Abstract While previous studies have focused on the benefits, risks and outcomes of buy–sell relationships, little is known about the dynamics of these relationships. Our study takes an initial step in this direction by examining how firms develop successful relationships. We review the literature and analyze multiple buyer–supplier relationships to explore developments over time, identify triggers for change, and identify effective management practices for long‐term inter‐organizational relationships. We employ retrospective data to compare six long‐standing buyer–supplier relationships. Our data suggest a recurring pattern of integration initiatives in the evolution towards a successful buy–sell relationship. Specifically, our field data indicate that this pattern starts with initiatives for logistics responsiveness , followed by knowledge exchange initiatives and finally initiatives to increase the use of common resources . Each of these initiatives are triggered by specific opportunities and are emergent in nature. By examining the triggers in the development and maintenance of buy–sell relationships, our study adds to the integration of existing life‐cycle frameworks, which increases our understanding of a life‐cycle theory for inter‐organizational relationships.